STUDI ANTRHROPOMETRY TRAKTOR TANGAN UNTUK OPERATOR DI LAHAN SAWAH - Arief RM Akbar; Sam Herodian; Suriani Ali (Jurnal Keteknikan Pertanian, 2007)
ABSTRACT This study was aimed to get ergonomic factors which influence working productivity and workload of operators in primary tillage operation according to specific land condition, environmental condition and local culture in South Kalimantan area. Artificial neural network models (ann) was used to formulate the non linear relationship among ergonomic factors of hand tractors. The ergonomic factors were anthropometry (height and width of hand tractor steer, age and weight of operators). The field measurment to determine working productivity of primery tillage used moldboard plow as hand tractors implement. Results of ann showed that working productivity in a range of 453 m2/h and 1284 m2/h and workload in a range of 106 p/m and 169 p/m. The younger operator have the best productivity. The model have accuracy of 89% for output model of working productivity and 96% for output model of workload in soil tillage. The Optimum result for height of steer in a range of 104 cm and 112 cm.Diterima: 2 Mei 2007, Disetujui: 17 Mei 2007